Comparison of RECIST version 1.0 and 1.1 in assessment of tumor response by computed tomography in advanced gastric cancer - Jang, Gil-Su (AME Publishing Company, 2013)
OBJECTIVE: Response Evaluation Criteria in Solid Tumors (RECIST) guideline version 1.0 (RECIST 1.0) was proposed as a new guideline for evaluating tumor response and has been widely accepted as a standardized measure. With a number of issues being raised on RECIST 1.0, however, a revised RECIST guideline version 1.1 (RECIST 1.1) was proposed by the RECIST Working Group in 2009. This study was conducted to compare CT tumor response based on RECIST 1.1 vs. RECIST 1.0 in patients with advanced gastric cancer (AGC). METHODS: We reviewed 61 AGC patients with measurable diseases by RECIST 1.0 who were enrolled in other clinical trials between 2008 and 2010. These patients were retrospectively re-analyzed to determine the concordance between the two response criteria using the κ statistic. RESULTS: The number and sum of tumor diameters of the target lesions by RECIST 1.1 were significantly lower than those by RECIST 1.0 (P<0.0001). However, there was excellent agreement in tumor response between RECIST 1.1 and RECIST 1.0 (κ=0.844). The overall response rates (ORRs) according to RECIST 1.0 and RECIST 1.1 were 32.7% (20/61) and 34.5% (20/58), respectively. One patient with partial response (PR) based on RECIST 1.0 was reclassified as stable disease (SD) by RECIST 1.1. Of two patients with SD by RECIST 1.0, one was downgraded to progressive disease and the other was upgraded to PR by RECIST 1.1. CONCLUSIONS: RECIST 1.1 provided almost perfect agreement with RECIST 1.0 in the CT assessment of tumor response of AGC.